Develop and design shematic diagram and mechanism on one seater drag buggy - Muhammad Ibrahim, Md Nujid (2008)
Development Buggy one seater is project continued from idea Mr Fazli and Mr Wong. The Buggy chassis is already finished by Mr faizul and I need upgrade or create transmission linkage the complete their system. Project need need to continue to make sure a Buggy finish until it can move and drive. The project also involves design and fabrication a rear engine transmission system by concerning the aspect the linkage, safety and don’t bother any system. The gear transmission system need to fabricate to make sure is suitable for the system. Modifications are required to improve the system. With a new concept of the linkage and mechanism, the analysis needed to approve the design. Mostly, this project is required to develop the skills in fabrication, design and testing. Whole of this project is particular involves suitable system of design and fabrication for transmission linkage and mechanism for Buggy. Diploma final year project will allocate the one semester to complete a project. This project also required the adequate student to finish a task given. The task division need to apply, for the entirely three part will be make that is a development of auxiliary system, steering system and transmission linkage system.